Composición mineral del agua de bebida en sistemas de producción lechera en Córdoba, Argentina - Pérez Carrera, Alejo Leopoldo (2007)
Dairy cattle drinking water in 28 medium and small farms located in the southeast of cordoba province, argentina, was analyzed in order to assess its beneficial and adverse effect in milk production. Total dissolved solids (tds), major ions, nitrates and trace metals were quantified by standardized methods. Water from the phreatic level is used in 62% of the selected farms, being its quality lower than that provided by deeper wells. Sodium chloride and sulfur requirements are provided by drinking water. Arsenic, fluoride and vanadium concentrations found in all phreatic samples are higher than the maximum allowed values recommended at international level.